Pernikahan Modern di Era Instagram: Analisis Semiotika Roland Barthes Pada Akun Instagram @thebridestory - Chasana, Rona Rizkhy Bunga (Program Fakultas Dakwah dan Ilmu Komunikasi (FDIKOM), UIN Syarif Hidayatullah Jakarta, 2023)
Instagram changed the way weddings are displayed in the media. Wedding professionals use Instagram as a tool to spread wedding fashion and culture. Bridestory has repeatedly become the official media at celebrity weddings who first shared wedding photos and videos exclusively through their Instagram accounts. This study wanted to find out how wedding culture is represented by @thebridestory. Some celebrity wedding photos will be dissected with Roland Barthes semiotics based on the Instagram aspect and the ritual aspect uploaded on @thebridestory Instagram account in 2016-2018. This study found 3 things related to representation of wedding culture in @thebridestory account. First, 1) western style as a symbol of modernity, 2) hybrid wedding as a combination of traditional culture and western style is also interpreted as a modern wedding. Finally, 3) the image of popular culture is then interpreted as an ideal image from the holding of a wedding to the meaning of the ideal bride.